Clinical and epidemiological features of pediatric population hospitalized with COVID-19: a multicenter longitudinal study (March 2020-December 2021) from PakistanResearch in context - Qalab Abbas; Farah Khalid; Fatima Farrukh Shahbaz; Javeria Khan; Shazia Mohsin; Murtaza Ali Gowa; Abdul Sattar Shaikh; Rai Muhammad Asghar; Javairia Khalid; Sehrish Karim; Fyezah Jehan; Masood Sadiq; et al. (Elsevier, 2023)
Summary: Background: We aimed to explore the epidemiological, clinical, and phenotypic parameters of pediatric patients hospitalized with COVID-19 in Pakistan. Methods: This longitudinal cohort study was conducted in five tertiary care hospitals in Pakistan from March 2020 to December 2021. Data on various epidemiological and clinical variables were collected using Case Report Forms (CRFs) adapted from the WHO COVID-19 clinical data platform at baseline and at monthly follow-ups for 3 months. Findings: A total of 1090 children were included. The median age was 5 years (Interquartile range 1-10), and the majority presented due to new signs/symptoms associated with COVID-19 (57.8%; n = 631), the most common being general and respiratory symptoms. Comorbidities were present in 417 (38.3%) children. Acute COVID-19 alone was found in 932 (85.5%) children, 81 (7.4%) had multisystem inflammatory syndrome (MIS-C), 77 (7.0%) had overlapping features of acute COVID-19 and MIS-C, and severe disease was found in 775/1086 (71.4%). Steroids were given to 351 (32.2%) patients while 77 (7.1%) children received intravenous immunoglobulins. Intensive care unit (ICU) care was required in 334 (31.6%) patients, and 203 (18.3%) deaths were reported during the study period. The largest spike in cases and mortality was from July to September 2021 when the Delta variant first emerged. During the first and second follow-ups, 37 and 10 children expired respectively, and medical care after discharge was required in 204 (25.4%), 94 (16.6%), and 70 (13.7%) children respectively during each monthly follow-up. Interpretation: Our study highlights that acute COVID-19 was the major phenotype associated with high severity and mortality in children in Pakistan in contrast to what has been observed globally. Funding: The study was supported by the World Health Organization (WHO), which was involved in the study design but played no role in its analysis, writeup, or publication.